Drug development strategies for the treatment of obesity: how to ensure efficacy, safety, and sustainable weight loss - Barja-Fernandez S; Leis R; Casanueva FF; Seoane LM (Dove Medical Press, 2014)
S Barja-Fernandez,1–3 R Leis,2 FF Casanueva,3,4 LM Seoane1,3 1Grupo Fisiopatología Endocrina, 2Departamento de Pediatría, Universidad de Santiago de Compostela (USC), Instituto de Investigación Sanitaria de Santiago de Compostela (IDIS), Complexo Hospitalario Universitario de Santiago (CHUS/SERGAS), Santiago de Compostela, Spain; 3CIBER Fisiopatologia de la Obesidad y Nutrición, Instituto de Salud Carlos III, Santiago de Compostela, Spain; 4Laboratorio de Endocrinología Molecular y Celular, Universidad de Santiago de Compostela (USC) Instituto de Investigación Sanitaria de Santiago de Compostela (IDIS), Complexo Hospitalario Universitario de Santiago (CHUS/SERGAS), Santiago de Compostela, Spain Abstract: The prevalence of obesity has increased worldwide, and approximately 25%–35% of the adult population is obese in some countries. The excess of body fat is associated with adverse health consequences. Considering the limited efficacy of diet and exercise in the current obese population and the use of bariatric surgery only for morbid obesity, it appears that drug therapy is the only available method to address the problem on a large scale. Currently, pharmacological obesity treatment options are limited. However, new antiobesity drugs acting through central nervous system pathways or the peripheral adiposity signals and gastrointestinal tract are under clinical development. One of the most promising approaches is the use of peptides that influence the peripheral satiety signals and brain–gut axis such as GLP-1 analogs. However, considering that any antiobesity drug may affect one or several of the systems that control food intake and energy expenditure, it is unlikely that a single pharmacological agent will be effective as a striking obesity treatment. Thus, future strategies to treat obesity will need to be directed at sustainable weight loss to ensure maximal safety. This strategy will probably require the coadministration of medications that act through different mechanisms. Keywords: obesity, energy balance, pharmacotherapy